Adverse selection among early adopters and unraveling innovation - Rory McGee (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2023)
I provide an equilibrium analysis of "selection markets": where consumers not only vary in how much they are willing to pay, but also in how much they cost to the seller. The model provides a joint explanation for three empirical phenomena: low uptake of existing products, slow demand for new products, and market inactivity despite unmet demand. I characterize when early adopters are more adversely selected in new markets. This lowers demand, increases costs, and leads markets to unravel prematurely. With endogenous market entry for new products (e.g., reverse mortgages, annuities), extended patents serve as de facto time-varying subsidies.
Keywords: 330